2021
DOI: 10.1101/2021.08.09.21261780
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vaccine safety surveillance using routinely collected healthcare data – An empirical evaluation of epidemiological designs

Abstract: Background: Routinely collected healthcare data such as administrative claims and electronic health records (EHR) can complement clinical trials and spontaneous reports when ensuring the safety of vaccines, but uncertainty remains about what epidemiological design to use. Methods: Using 3 claims and 1 EHR database, we evaluate several variants of the case-control, comparative cohort, historical comparator, and self-controlled designs against historical vaccinations with real negative control outcomes (outcome… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…For example, Li et al recently found that historical comparisons had Type II errors ranging between 0% to 10% and Type I errors above 30% [18]. Age and sex adjustment reduced Type I error, had little impact on Type II error, and improved precision in some cases [16]. Historical rate comparison was, overall, good at identifying true safety signals [16].…”
Section: Key Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, Li et al recently found that historical comparisons had Type II errors ranging between 0% to 10% and Type I errors above 30% [18]. Age and sex adjustment reduced Type I error, had little impact on Type II error, and improved precision in some cases [16]. Historical rate comparison was, overall, good at identifying true safety signals [16].…”
Section: Key Resultsmentioning
confidence: 99%
“…Age and sex adjustment reduced Type I error, had little impact on Type II error, and improved precision in some cases [16]. Historical rate comparison was, overall, good at identifying true safety signals [16]. Based on Li et al's results, we evaluated the age and sex adjusted variant for historical comparator, using a time-at-risk of 1-28 days after the historic visit, for both first and second doses.…”
Section: Key Resultsmentioning
confidence: 99%
See 3 more Smart Citations